Pixantrone–rituximab versus gemcitabine–rituximab in relapsed/refractory aggressive non-Hodgkin lymphoma. (August 2016) - Belada, David; Georgiev, Pencho; Dakhil, Shaker; Inhorn, Lowell F; Andorsky, David; Beck, J Thaddeus; Quick, Donald; Pettengell, Ruth; Daly, Robert; Dean, James P; Pavlyuk, Mariya; Failloux, Nelly; et al.
We describe the rationale and design of the ongoing randomized, active-controlled, multicenter, Phase III study evaluating the efficacy of pixantrone and rituximab versus gemcitabine and rituximab in patients with diffuse large B-cell lymphoma or follicular grade 3 lymphoma, who are ineligible for high-dose chemotherapy and stem cell transplantation, and who failed front-line regimens containing rituximab. The administration schedule is pixantrone 50 mg/m 2 intravenously (iv.) or gemcitabine 1000 mg/m 2 iv. on days 1, 8 and 15, combined with rituximab 375 mg/m 2 iv. on day 1, up to six cycles. Pixantrone has a conditional European marketing approval for monotherapy in adults with multiple relapsed or refractory aggressive B-cell non-Hodgkin lymphoma. Our trial explores the efficacy of combining pixantrone with rituximab and completes postauthorization measures. Trial registration number: NCT01321541.